ДЕРЖАВНА ПОЛІТИКА СТИМУЛЮВАННЯ ГРОШОВИХ ПЕРЕКАЗІВ ТРУДОВИХ МІГРАНТІВ: ЗАРУБІЖНИЙ ДОСВІД ТА ВІТЧИЗНЯНІ РЕАЛІЇ - Кізима, Тетяна Олексіївна; Онищук, Вікторія Олегівна (Науковий журнал «Світ фінансів», 2017)
Кізима Т. О., Онищук В. О. Державна політика стимулювання грошових переказів трудових мігрантів: зарубіжний досвід та вітчизняні реалії. Розглянуто теоретико-методологічні засади формування грошових переказів трудових мігрантів, а також проаналізовано їх обсяг, канали і напрями використання. Наголошено на ключових проблемах, пов’язаних із об’єктивною оцінкою обсягів міграційного капіталу та забезпечення чіткої державної політики регулювання доходів трудових мігрантів. Зазначено переваги та визначено ризики стимулювання грошових надходжень від трудових мігрантів. Окреслено зарубіжний досвід регулювання грошових переказів трудових мігрантів. Надано рекомендації щодо державної політики України в сфері регулювання міграційного капіталу. Кизыма Т. А., Оныщук В. О. Государственная политика стимулирования денежных переводов трудовых мигрантов: зарубежный опыт и отечественные реалии. Рассмотрены теоретико-методологические основы формирования денежных переводов трудовых мигрантов, а также проанализирован их объем, каналы и направления использования. Отмечены ключевые проблемы, связанные с объективной оценкой объемов миграционного капитала и обеспечения четкой государственной политики регулирования доходов трудовых мигрантов. Указаны преимущества и определены риски стимулирования денежных поступлений от трудовых мигрантов. Проанализирован зарубежный опыт регулирования денежных переводов трудовых мигрантов. Обоснованы направления совершенствования государственной политики Украины в сфере регулирования миграционного капитала. Kizyma T., Onyshchuk V. State policy in migrant remittances incitement: international experience and domestic realities. Introduction. State policy of incomes regulation of migrant workers is an important component of social policy, as sustainable economic development, people’s welfare increase is impossible without the formation of socially rightful and economically prosperous society. Purpose lies in reasoning the economic essence of remittances, as well as analysis of the main vectors of state policy in the income regulation of from labour migration with appropriate verification of existing problems and outlining suggestions for its improvement in current conditions. Results. Considering this study we suggest: improving the mechanism of remittances, encourage remittances from labour migrants to increase their volumes; create conditions for the productive use of remittances; direct transfers for the benefit of small business; increase the level of financial literacy of migrants and their families; promote legal and organized migration; establish close links with the diaspora, and etc. Conclusion. The maximal effort should be made to civilize the migration processes, in order to launch successfully all the infrastructural chains of departure, employment, transfer of funds, returning emigrants back to their motherland. If the authorities fulfill this, millions of workers will reward them with the significant increase in remittances into Ukraine, new knowledge, experience, innovation, investment, creation of new enterprises at home, and therefore, new workplaces.